2019
DOI: 10.1021/acs.joc.9b02473
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Component Derivatization Protocol for Determining the Enantiopurity of Sulfinamides by 1H and 19F NMR Spectroscopy

Abstract: A practically simple three-component chiral derivatization protocol has been developed to determine the enantiopurity of eight S-chiral sulfinamides by 1H and 19F NMR spectroscopic analysis, based on their treatment with a 2-formylphenylboronic acid template and enantiopure pinanediol to afford a mixture of diastereomeric sulfiniminoboronate esters whose diastereomeric ratio is an accurate reflection of the enantiopurity of the parent sulfinamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…each) to minimize kinetic resolution and/or epimerisation of -amino ester salts 61. Finally, a recent study on all four regioisomers of fluoro-2-FPBA as bifunctional templates for analysis of the ee's of sulfinamides revealed that 3-fluoro-2-FPBA 3-F-1 was the optimal template (Figure 6), [57] producing an impressive chemical shift difference of ∆δF = -2.328 ppm between the IBE diastereomers produced from Ellman's sulfinamide (Figure 6b). A stepwise approach was used to derivatise a small range of sulfinamides 34, 3-F-1 and (1R,2R,3S,5R)-pinanediol 36 which gave large chemical shift differences and full baseline resolution of the imine and fluorine peaks of their diastereomeric IBE complexes.…”
Section: F Nmr Spectroscopic Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…each) to minimize kinetic resolution and/or epimerisation of -amino ester salts 61. Finally, a recent study on all four regioisomers of fluoro-2-FPBA as bifunctional templates for analysis of the ee's of sulfinamides revealed that 3-fluoro-2-FPBA 3-F-1 was the optimal template (Figure 6), [57] producing an impressive chemical shift difference of ∆δF = -2.328 ppm between the IBE diastereomers produced from Ellman's sulfinamide (Figure 6b). A stepwise approach was used to derivatise a small range of sulfinamides 34, 3-F-1 and (1R,2R,3S,5R)-pinanediol 36 which gave large chemical shift differences and full baseline resolution of the imine and fluorine peaks of their diastereomeric IBE complexes.…”
Section: F Nmr Spectroscopic Analysismentioning
confidence: 97%
“…Consequently, a stepwise 'one-pot' two-component protocol was developed based on initial reaction of 2-FPBA 1 with a sulfinamide 34 to afford a sulfiniminoboronic acid intermediate 35, whose boronic acid fragment was then reacted with pinanediol 36 to afford the desired sulfiniminoboronate ester complexes 37 (Scheme 19). [57] This stepwise protocol was successfully applied to 8 racemic sulfinamides, which resulted in baseline-resolved imine signals for their diastereomeric IBEs in their 1 H NMR spectra in all instances, with no evidence of kinetic resolution.…”
Section: Sulfinamidesmentioning
confidence: 99%
“…The change of the chemical shift as a result of structural changes in the molecule is visible even for the peripheral fluorine atoms, which was the basis for the concept of using the “fluorine tag” [ 61 ]. The derivatives of the fluorinated boronic acids were used for diol sensing in combination with 19 F NMR spectroscopy [ 62 , 63 ], as well as in a derivatization protocol for determination of the enantiopurity of sulfonamides [ 64 ]. The esterification of bisboronic compounds with fluorinated diols was also studied [ 65 ].…”
Section: Nmr Characterizationmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy is an essential analytical tool in organic chemistry, where the technique’s primary value lies in its potential for determining chemical identity through characterizing molecular structure . NMR serves as a principle means of investigating aspects such as molecular conformation and enantiopurity, and the continuous development of new methods expands upon this potential to encompass novel applications such as quantifying metal–ligand complexes’ relative Lewis acidity and real-time enzymatic reaction monitoring. The technique thus exhibits remarkable disciplinary value, though unfortunately, research demonstrates that individuals often struggle to successfully evaluate NMR spectra in the absence of significant research and classroom experience In addition to these resources, the organic chemistry community requires an understanding of how expertise in this practice develops.…”
Section: Introductionmentioning
confidence: 99%